Automatic Coffee Maker Machine Based on Internet of Things (IoT) - Akbar Sujiwa; Iwan Santoso (BEST, 2022)
In this era of globalization, technological developments are very rapid penetrated in all fields in particular. in the food and beverage sector..During a pandemic like this, as entrepreneurs, food and drink must adapt. Adaptation in question is hygiene in the process of making drinks and food. One example. it is an automatic drink making machine. that can help in the process. make drinks more practical and hygienic to keep more sterile. when making drinks in terms of blending drink ingredients. the process of stirring and pouring hot water. In an automatic drink making machine, in a supermarket there are still many weaknesses. ie the user is still making physical contact, such as approaching and selecting the menu and waiting for the process to complete. Based on the problems that exist among the general public, an idea was formed to design and manufacture an Internet of Things (IOT) based automatic drinking machine. which can help users in terms of making a drink. Users only need to select the drink menu that they want to make on the Android smartphone application that is connected to the access point, then the machine will carry out the process of making drinks. according to the menu selected in the application. The user only takes drinks to the places that are available. Based on the results of testing and analysis carried out on a machine this helps users to place orders and can enjoy drinks that are processed automatically.